Hydroxyapatite-ZnO Biomimetic Toothpaste Formulation from Rice Snail Shell Waste - Wisaeni Intannia; Charlena Charlena; Irma Herawati Suparto (Science and Technology Indonesia, 2023)
Toothpaste is a preparation for dental treatment to clean, beautify, and replace minerals that decay from the surface of the teeth. Prevention of damage to the mineral layer of the teeth, the addition of remineralizing agents to toothpaste preparations in the form of hydroxyapatite-ZnO composites is carried out. This study aims to synthesize and characterize hydroxyapatite-ZnO, as well as to formulate hydroxyapatite-ZnO toothpaste from rice field conch shell waste. Hydroxyapatite-ZnO composites have been successfully synthesized using the sol-gel method and characterized using X-Ray Diffraction (XRD), Fourier Transform Infra-Red (FTIR), and Scanning Electron Microscope-Energy Dispersive X-Ray (SEM-EDX). The XRD result obtained a crystal size of 59.90 nm with a crystallinity percentage of 68.85%. The absorption band at a wave number of 452 cm−1 is an indication that the ZnO compound has been successfully combined with hydroxyapatite. SEM-EDX analysis showed that the morphology of the compound was granular with a rough surface, uneven size, and shape. The results of the hydroxyapatite-ZnO toothpaste formulation in the 45% formula had good physical stability compared to other formulas. The antibacterial properties of hydroxyapatite-ZnO toothpaste preparations showed a very strong inhibitory effect on Streptococcus mutans bacteria. The results of the hydroxyapatite-ZnO toothpaste formulation in the 45% formula had good physical stability compared to other formulas. The antibacterial properties of hydroxyapatite-ZnO toothpaste preparations showed a very strong inhibitory effect on Streptococcus mutans bacteria. The results of the hydroxyapatite-ZnO toothpaste formulation in the 45% formula had good physical stability compared to other formulas. The antibacterial properties of hydroxyapatite-ZnO toothpaste preparations showed a very strong inhibitory effect on Streptococcus mutans bacteria.